2017
DOI: 10.1016/j.ymgmr.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Immune tolerance induction for laronidase treatment in mucopolysaccharidosis I

Abstract: Enzyme replacement therapy (ERT) can produce anti-drug antibody (ADA) responses that reduce efficacy or lead to hypersensitivity reactions. Six patients with severe mucopolysaccharidosis type I (MPS I/Hurler syndrome) who did not receive hematopoietic stem cell transplantation underwent an immunosuppression regimen prior to initiating ERT with laronidase. The primary endpoint for immune tolerance induction was the number of patients with an ADA titer ≤ 3200 after 24 weeks of laronidase at the labeled dose. Cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
(39 reference statements)
0
10
0
1
Order By: Relevance
“…More detailed information on causes of death in the ERT group may have provided additional insights into whether certain organ systems are differentially improved or burdened in the long term. As monitoring anti-drug antibody responses is an increasingly recognized factor in ERT success 15 , 39 , 40 , this study cannot account for the degree to which it affected outcomes of the ERT group. However, a recent meta-analysis demonstrated that antibody titers generally decrease over time during treatment with ERT 40 , and while this may not be true for every patient, a more comprehensive examination of one of the patients from this group revealed that even though anti-ERT antibodies doubled in a 6-year span, there was no apparent impact on efficacy for her 13 .…”
Section: Discussionmentioning
confidence: 99%
“…More detailed information on causes of death in the ERT group may have provided additional insights into whether certain organ systems are differentially improved or burdened in the long term. As monitoring anti-drug antibody responses is an increasingly recognized factor in ERT success 15 , 39 , 40 , this study cannot account for the degree to which it affected outcomes of the ERT group. However, a recent meta-analysis demonstrated that antibody titers generally decrease over time during treatment with ERT 40 , and while this may not be true for every patient, a more comprehensive examination of one of the patients from this group revealed that even though anti-ERT antibodies doubled in a 6-year span, there was no apparent impact on efficacy for her 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to prevent ADA responses to ERT were seldom described. An immune tolerance induction regimen based on cyclosporin A and azathioprine was ineffective in patients with MPS IH as well as monotherapy with methotrexate [217,218]. Another immune tolerance induction regimen was used in a 4-year-old MPS II boy, with sustained high ADAs titer and limited clinical efficacy of idursulfase treatment.…”
Section: Immunogenicitymentioning
confidence: 99%
“…Impacts on Pompe patients are often cited as the most dramatic example, where children show significant improvement in motor milestones in response to ERT only to have these effects rapidly reversed upon induction of neutralizing antibodies, leading eventually to patient death [16,18,19]. Tolerization protocols have been tested for patients where ERT efficacy is blocked by immune responses but these treatments might not be efficacious [20], are intensive for patients, and pose significant risks of infection or malignancy [16]. Gene therapy approaches are currently under development for LSDs as an alternative to ERTs.…”
Section: Lysosomal Storage Diseases and The Need For Widespread Biodimentioning
confidence: 99%